If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2s + -1) + -3 = -3(6s + 6) + -3 Reorder the terms: -3(-1 + 2s) + -3 = -3(6s + 6) + -3 (-1 * -3 + 2s * -3) + -3 = -3(6s + 6) + -3 (3 + -6s) + -3 = -3(6s + 6) + -3 Reorder the terms: 3 + -3 + -6s = -3(6s + 6) + -3 Combine like terms: 3 + -3 = 0 0 + -6s = -3(6s + 6) + -3 -6s = -3(6s + 6) + -3 Reorder the terms: -6s = -3(6 + 6s) + -3 -6s = (6 * -3 + 6s * -3) + -3 -6s = (-18 + -18s) + -3 Reorder the terms: -6s = -18 + -3 + -18s Combine like terms: -18 + -3 = -21 -6s = -21 + -18s Solving -6s = -21 + -18s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '18s' to each side of the equation. -6s + 18s = -21 + -18s + 18s Combine like terms: -6s + 18s = 12s 12s = -21 + -18s + 18s Combine like terms: -18s + 18s = 0 12s = -21 + 0 12s = -21 Divide each side by '12'. s = -1.75 Simplifying s = -1.75
| 42xy+56x-6y-8=0 | | 9n+-3=7(n+3)+2n | | f(x)=-11.246 | | 6y+4=25 | | X^2=48/16 | | -6v=-7 | | x+2x+3x+4x=132 | | Fg-9h=10jsolv | | Fg-9h=10jsolve | | c(2c+3)+6(2c+3)= | | -3(4s-2)-6=-3(7s+1)-5 | | 7(7x/1) | | f(x)=-27.083x-16.819 | | -2+3x+7-7x=-29 | | 12+x+4x-4+3x+3=180 | | 4n-9n-n= | | 6x-4=26-4x | | 2sin^2x-5sinx-2=0 | | 3/4m=7.5 | | 19x+20+x+10=90 | | x+x+x+x=44 | | 1e+18= | | x/6=3/9 | | -2(4s-5)-10=-3(5s+5)-5 | | 3n+3=-4 | | 123456789-987654321=0 | | (9-10)x= | | -6x^2+5x+6=7.01466 | | 1x+1-2-(3-x)=6-(1-1) | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | 17-x=33(x+7) | | 6-2(3x-4)=12 |